Implementation of a Model for Using Methods to Improve Professional Competence in Teaching Social and Humanitarian Sciences in Medical Higher Education Institutions - Khamroyev Rustam Rasulovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The development of modern medical education requires an integrated approach to forming not only clinical knowledge but also essential social, ethical, and humanitarian competencies. Effective teaching of social and humanitarian sciences plays a critical role in preparing future medical professionals for complex interpersonal interactions, ethical decision-making, and culturally sensitive patient care. This article presents a pedagogical model designed to enhance professional competence through innovative teaching methods in medical higher education institutions. The model includes conceptual, technological, and evaluative components and provides strategies for integrating interactive, problem-based, and reflective methods into the curriculum. The analysis demonstrates that the implementation of such a model significantly improves students’ communication abilities, ethical reasoning, social awareness, and professional responsibility. The article concludes with recommendations for institutional integration and further development of competence-oriented medical education.